1999
DOI: 10.1080/09629359990414
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationship of the Kinin System, Nitric Oxide and Eicosanoids in the Antigen‐Induced Arthritis in Rabbits

Abstract: The aim of the present study was to investigate the interrelationship of the kinin system, nitric oxide and eicosanoids in the acute phase of antigen-induced arthritis (AIA) in rabbits. The arthritis was induced in immunized rabbits and the following parameters were evaluated 24 hours later: leukocyte influx (total and differential white cell count), vascular permeability (Evans's blue method), and synovial PMN cell infiltrate. PGE2 and LTB4 (radioimmunoassay) levels were quantified in the synovial fluid. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 36 publications
3
9
0
Order By: Relevance
“…We had already demonstrated that rabbits submitted to the same pharmacological treatment had reduction in cellular recruitment and vascular permeability on arthritis induced even by BjV or by serum albumin bovine [9,[30][31][32]. Additionally, the reduced inflammatory response observed in L-NAME treated rats is in agreement with other experimental studies which employed different schedules of treatments and stimulus [48 -51].…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…We had already demonstrated that rabbits submitted to the same pharmacological treatment had reduction in cellular recruitment and vascular permeability on arthritis induced even by BjV or by serum albumin bovine [9,[30][31][32]. Additionally, the reduced inflammatory response observed in L-NAME treated rats is in agreement with other experimental studies which employed different schedules of treatments and stimulus [48 -51].…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies demonstrated that in vitro incubation with NOS inhibitors attenuates subsequent chemotaxis of polymorphonuclear cells [52 -55]. It is important to note that this protocol of treatment also promoted reduction on IL1 and eicosanoids levels on inflammatory exudates, which may contribute to the impairment of the inflammatory reaction [9,30,32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of NO in the AIA joints, on the other hand, represents a clear difference in comparison with human RA [4] and experimental arthritides, such as AIA in rabbits [34] and rats [20]. Since the presence of inhibitors of the NO detection assay was excluded, the present findings probably reflect species differences in the AIA model.…”
Section: Cytokine Profile During Acute Aiamentioning
confidence: 61%